Gender, sexualisation and feminism in Salsa: Interrelations of strong women and sexualisation in the Klang Valley / Santha Chandherasegaran - Santha, Chandherasegaran (2016)

(untitled)
Salsa, a dance that is highly sexualised today as it comprises of sexy and erotic elements has been globally commercialised. The erotic elements in this global salsa is primarily executed by female dancers. This global salsa has spread rapidly in the Klang Valley. This study is carried out in the field of ethnochoreology and attempts to explore the sexualisation of salsa dancing within the context of gender and feminism. The sexualisation of salsa is explored to leverage feminism amongst female participants. An analysis of qualitative research of salsa clubs and studios in the Klang Valley through gender and feminist theories is used in this study. This study offers rich new perspectives of linking sexualisation of salsa in the Klang Valley with power and control as opposed to the sexual objectification of the female body. Keywords: Feminism, Gender, Commercialised, Sexualisation, Erotic, Salsa, Ethnochoreology, Strong Women, Female Body